Increasing incidence of nonlethal inflicted injuries in paediatric homicides: A 45-year study. (October 2018) - Pilla, Mark; van den Heuvel, Corinna; Musgrave, Ian; Byard, Roger W.
Abstract: A retrospective study was undertaken at Forensic Science South Australia of all homicides in individuals aged <18 years from January 1970 to December 2014. 166 cases were identified (M:F = 1.5:1). The number of cases steadily declined, with the highest numbers and death rate occurring between 1970 and 1974 (N = 26; 0.37/100, 000 population), and the lowest between 2010 and 2014 (N = 8; 0.1/100, 000) (p < 0.01). Deaths were due to blunt force trauma (37%), gunshot wounds (19%), asphyxiation (18%), sharp force trauma (8%), poisoning (8%), burns (3%) and neglect (1%), or were undetermined (6%). There was a significant increase in numbers of accompanying nonfatal injuries (3.46 per case for 1970 and 1974, compared to 18.88 per case for 2010 and 2014). Thus, while both the absolute numbers and the rates of paediatric homicides declined significantly, numbers of nonlethal injuries increased. Whatever the underlying reason(s) for the increase in nonlethal injuries, fatal attacks on children in South Australia appear to be becoming more violent. Highlights: 166 cases of homicides in individuals aged <18 years were studied (1970–2014). The number of cases steadily declined, with 26 cases between 1970–1974 and 8 between 2010–2014. Most deaths were due to blunt force trauma (37%), gunshot wounds (19%), and asphyxiation (18%). There was a significant increase in numbers of accompanying nonfatal injuries: 3.46–18.88/case. Fatal attacks on children were becoming more violent over time in this study.